Exploring Characteristic of Women Leadership in Socio-Religious Organization The Catholic Woman of The Republic Of Indonesia South Kalimantan Region - Melania Melania; Anthonius Junianto Karsudjono; Amiartuti Kusmaningtyas; Tri Ratnawati (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2021)
Leadership often associated with certain age, gender, or race that causes someone considered not good enough to be promoted in a particular position, even in this era it is still prevents women from becoming leaders, even though they have a huge opportunity to be able to practice being a leader. So there is a difficulty of finding cadres who "voluntarily" are willing to be nominated to lead at the Regional level. The aim of this research are to explore the indicator of women leadership; strengths – weaknesses – opportunities – challenges of women to become a leader; and to build women leadership character in socio-religious organization the Catholic Woman of the Republic of Indonesia   South Kalimantan region. Using qualitative descriptive method. Data collected through open-ended questions with competent informants, exploring internal-external factors using SWOC analysis, building leadership character refers to the Malcolm Baldrige criteria on leadership. The result of the research show that women have difficulty in managing their time and priorities between family-career-organizations, so they ignore many opportunities that they can actually get.The expected leadership indicators are: must be able to develop the organization, have a sense of responsibility, discipline, effective communication,  willing to serve,  assertive, authoritative, good personality.